2015
DOI: 10.1002/jso.24024
|View full text |Cite
|
Sign up to set email alerts
|

Transthoracic versus transhiatal resection for esophageal adenocarcinoma of the lower esophagus: A value‐based comparison

Abstract: Background and Objective Our objective was to compare clinical outcomes, costs, and resource use based on operative approach, transthoracic (TT) or transhiatal (TH), for resection of esophageal cancer. Methods This cohort analysis utilized the Surveillance, Epidemiology, and End Results—Medicare linked data from 2002 to 2009. Only adenocarcinomas of the lower esophagus were examined to minimize confounding. Medicare data was used to determine episode of care costs and resource use. Propensity score matching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 29 publications
(54 reference statements)
2
26
2
Order By: Relevance
“…Few details are known regarding the specific costs and factors associated with the costs of complications after esophagectomy [9][10][11]. Such data are needed to improve quality and value after esophagectomy.…”
mentioning
confidence: 99%
“…Few details are known regarding the specific costs and factors associated with the costs of complications after esophagectomy [9][10][11]. Such data are needed to improve quality and value after esophagectomy.…”
mentioning
confidence: 99%
“…In such cases, second thoracotomy would be a more invasive method for the patients. Another important issue is that, as in our study, many cases with appearance of invasion in the conventional thoracic CT and conventional MRI are not actually T 4 . Surgery operation should not be delayed in suitable patients with the absence of invasion by cine-MRI.…”
Section: Discussionmentioning
confidence: 57%
“…In addition, favorable preoperative assessment and postoperative care are of utmost importance for the success. [4,5] Staging of esophageal cancer has a major role in determining grade of the disease, planning of treatment, and prognosis. In the preoperative staging of esophageal cancer, endoscopic ultrasonography (EUS), positron emission tomography (PET), computed tomography (CT), multi-detector computed tomography (MDCT), and magnetic resonance imaging (MRI) are used.…”
mentioning
confidence: 99%
“…Whether extensive LND can improve 5-year survival rate remains debatable. Some studies showed that 5-year survival rates were not significantly different between the extended LND via transthoracic and limited LND via transhiatal for esophageal adenocarcinoma (13)(14)(15). Despite no significant difference, other studies showed a trend toward improved 5-year survival with the extended transthoracic approach (6,7,16,17).…”
Section: Discussionmentioning
confidence: 99%